Spatial mobility and returns to education: some evidence from a sample of French youth - Philippe Lemistre; Nicolas Moreau (Institute for the Study of Labor (IZA), 2006)
The purpose of this article is to reevaluate the returns to geographic mobility and to the level of education, taking into account the interaction between these two variables. We have at our disposal an original French database that permits precise calculation of the distance between the place of education and the location of first employment. We thus capture mobility without a priori regarding the geographical areas selected, and we use kilometric thresholds to estimate the returns to spatial mobility. Our results suggest decreasing returns to spatial mobility as the distance covered rises and increasing returns to mobility with higher levels of education. In addition, for all levels of education, including the lowest, returns to geographic mobility prove to be positive, for one threshold at least and several distances
urn:nbn:de:101:1-20090406296
Keywords: 330; Regionale Arbeitsmobilität; Bildungsertrag; Jugendliche; Frankreich